Pedagogical Communication of Generation Y History Teachers in Digital-Era History Learning for Generation Z Students at SMA Petra 4 Sidoarjo - Aprillia Ayu Tri Widyaningrum; Riyadi (Darul Yasin Al Sys, 2026)
Digital transformation has reshaped how Generation Z students access information, communicate, and participate in learning, requiring teachers to adapt their pedagogical communication accordingly. This study examined how Generation Y history teachers adapted their communication practices to the characteristics of Generation Z students in digital-era history learning at SMA Petra 4 Sidoarjo. A qualitative case-study design was employed, with data collected through in-depth interviews, participant classroom observations, and documentation from February to April 2026. The analytical framework operationalized stimulus, organism, and response components to connect teachers’ verbal messages, digital media, and instructional methods with students’ characteristics and learning responses. Data were analyzed through the interactive processes of data reduction, data display, and conclusion drawing and verification. Credibility was strengthened through source, technique, and time triangulation. The findings indicate that students responded most positively to audiovisual media, two-way communication, discussions, contextual examples, feedback, and positive reinforcement. Generation Y teachers integrated Canva, learning videos, electronic modules, learning management systems, educational games, verbal and nonverbal communication, and dialogic interaction. These practices were qualitatively associated with increased motivation, participation, attention, conceptual understanding, and confidence in expressing opinions. However, students’ multitasking remained a persistent barrier to sustained attention. The study concludes that effective intergenerational pedagogical communication in history education requires multimodal, dialogic, and contextually relevant strategies alongside deliberate efforts to manage digital distraction.